2013
DOI: 10.1152/ajpcell.00038.2012
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid supplementation enhances in vitro skeletal muscle cell growth via a COX-2-dependent pathway

Abstract: [e.g., prostaglandins (PGs), leukotrienes, and hydroxyeicosatetraenoic acids] has been implicated in skeletal muscle cell growth and development. The collective role of AA-derived metabolites in physiological states of skeletal muscle growth/atrophy remains unclear. The present study aimed to determine the direct effect of free AA supplementation and subsequent eicosanoid biosynthesis on skeletal myocyte growth in vitro. C2C12 (mouse) skeletal myocytes induced to differentiate with supplemental AA exhibited do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 61 publications
(114 reference statements)
1
59
0
3
Order By: Relevance
“…A similar relation of n-6 and n-3 to birth weight has been described previously, especially for C20:4n-6 [45,47]. C20:4n-6 acts as precursor for growth-related prostaglandins [48]. In a recent study, lower maternal n-3 polyunsaturated fatty acid (PUFA) concentrations and higher n-6 PUFA concentrations during pregnancy were associated with higher body fat and abdominal fat in children of a large population-based, prospective cohort study [49].…”
Section: Discussionmentioning
confidence: 55%
“…A similar relation of n-6 and n-3 to birth weight has been described previously, especially for C20:4n-6 [45,47]. C20:4n-6 acts as precursor for growth-related prostaglandins [48]. In a recent study, lower maternal n-3 polyunsaturated fatty acid (PUFA) concentrations and higher n-6 PUFA concentrations during pregnancy were associated with higher body fat and abdominal fat in children of a large population-based, prospective cohort study [49].…”
Section: Discussionmentioning
confidence: 55%
“…Muscle tissue is a potential source of certain lipid mediators, especially PGs, which are known to be synthesized locally by muscle cells (55). Numerous potential nonmuscle sources of lipid mediators also exist, however, including neutrophils (PGs and LTs), platelets (TXB 2 and 12-HETE), monocytes/macrophages (15-HETE), vascular endothelial cells (PGI 2 ), and transcellular interactions (lipoxins and resolvins).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] In 1978, Horwitz et al 55 observed that the fatty acids added to the culture medium have a stimulatory effect on the fusion of embryonic myoblasts. The authors observed that the lipid composition of the membrane influences the proliferation and fusion of myoblasts and, consequently, the formation of multinucleated myotubes.…”
Section: Effects Of Fatty Acids On Muscle Cell Differentiationmentioning
confidence: 99%
“…There is evidence that fatty acids modulate muscle function and trophism. [7][8][9][10][11] Our article is the first to describe and discuss the effects of fatty acids, especially oleic and linoleic acids, which are the most abundant fatty acids in Western diets, on muscle plasticity and trophism, with emphasis on skeletal muscle regeneration and in vitro differentiation of muscle cells. This is the main focus of our review.…”
Section: Introductionmentioning
confidence: 99%